Interferons and Resistance Mechanisms in Tumors and Pathogen-Driven Diseases—Focus on the Major Histocompatibility Complex (MHC) Antigen Processing Pathway - Chiara Massa (14175563) (2023)
Interferons (IFNs), divided into type I, type II, and type III IFNs represent proteins that are secreted from cells in response to various stimuli and provide important information for understanding the evolution, structure, and function of the immune system, as well as the signaling pathways of other cytokines and their receptors. They exert comparable, but also distinct physiologic and pathophysiologic activities accompanied by pleiotropic effects, such as the modulation of host responses against bacterial and viral infections, tumor surveillance, innate and adaptive immune responses. IFNs were the first cytokines used for the treatment of tumor patients including hairy leukemia, renal cell carcinoma, and melanoma. However, tumor cells often develop a transient or permanent resistance to IFNs, which has been linked to the escape of tumor cells and unresponsiveness to immunotherapies. In addition, loss-of-function mutations in IFN signaling components have been associated with susceptibility to infectious diseases, such as COVID-19 and mycobacterial infections. In this review, we summarize general features of the three IFN families and their function, the expression and activity of the different IFN signal transduction pathways, and their role in tumor immune evasion and pathogen clearance, with links to alterations in the major histocompatibility complex (MHC) class I and II antigen processing machinery (APM). In addition, we discuss insights regarding the clinical applications of IFNs alone or in combination with other therapeutic options including immunotherapies as well as strategies reversing the deficient IFN signaling. Therefore, this review provides an overview on the function and clinical relevance of the different IFN family members, with a specific focus on the MHC pathways in cancers and infections and their contribution to immune escape of tumors. Other Information Published in: International Journal of Molecular Sciences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/ijms24076736